Academic Outcomes in Bilingual Children With Developmental Language Disorder: A Longitudinal Study - Aguilar-Mediavilla, Eva; Buil-Legaz, Lucía; López-Penadés, Raül; Sanchez-Azanza, Victor A.; Adrover-Roig, Daniel (Frontiers in Psychology, 2019)
Previous studies have shown that most English-speaking children with language difficulties show academic difficulties during their schooling. The present study aimed to describe the academic achievement of children speaking Spanish and Catalan with developmental language disorder (DLD) during their primary education and to predict their academic outcomes using several processing skills assessed at the beginning of their schooling. To this end, we followed 28 children during their schooling (6–12 years of age). Participants were divided into two groups, one with DLD (n = 14) and a control group (n = 14) paired by age, gender, socio-economic status (SES), family language (L1), and classroom. All participants were assessed through different processing skills with the Spanish version of the NEPSY at the beginning of their schooling (age 6): attention (visual attention, auditory attention, and response set), phonological awareness, verbal short-term memory (sentence repetition, and narrative memory), access to language (semantic verbal fluency and rapid naming), and language comprehension (comprehension of verbal commands). At the end of primary education, schools reported the official academic marks at the 1st cycle (6–8 years), 2nd cycle (8–10 years) and 3rd cycle (10–12 years). Direct scores of the processing skills and academic results were used for statistical analyses. Results showed that children with DLD had more frequent grade retention, and their academic marks were significantly lower than those of their peers in all the cycles and for all academic subjects with a high language dependency (all except physical education and mathematics). Those subjects with lower language dependence did not show significant differences (physical education and mathematics). Rapid naming accounted for most of the variance of academic outcomes, followed by phonological awareness, and language comprehension when both groups were taken together. Only rapid naming accounted for academic results in the DLD group and phonological awareness did so for the control group. In sum, children with DLD experienced more academic difficulties during their primary education. Those children (with and without DLD) who experienced difficulties not only with rapid naming but also with phonological awareness and oral language comprehension at the beginning of their schooling showed a higher probability of academic failure.